Using Edmodo as a Media of E-Learning Learning in Educational Technology Courses - Thoiyibi, Muhammad; Nuzli, Muhammad (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Abstract: New concepts in IT-based learning, often known as e-learning, were born because of the use of technology in the learning process. Teachers can choose from a variety of online learning media as a medium of learning in e-learning, one of which is Edmodo. Edmodo is a Non-Governmental Organization (NGO) that offers several tools for instructors to use in their classrooms. The purpose of this study is to describe the usage of Edmodo as an e-learning medium in pai class education technology courses, to determine Civitas Academica's reaction to Edmodo as an e-learning medium, and to determine the benefits and drawbacks of Edmodo as an e-learning medium. This study employs a qualitative technique in conjunction with descriptive analysis. Interviews, observations, and documentation were utilized to collect data in this study, which were aided by research equipment in the form of interview grids. There are additional guidelines for observation. This study took place in PAI classes, with 70 students and teachers from Educational Technology courses serving as the primary informants. The findings of this study revealed that Edmodo can be used as a supplemental class in PAI classes and that PAI students can benefit from the use of PAI. Edmodo as an e-learning learning medium, teachers are also greatly aided by its existence; as an e-learning learning medium, Edmodo has many advantages, particularly in terms of features offered, and the disadvantages of using Edmodo as an e-learning learning medium are highly dependent on the internet network.